Promoting the use of point of care testing in non-communicable disease screening among university students - Pauline Tendai Maniki; Razeeya Khan; Ane Orchard; Stephanie De Rapper; Neelaveni Padayachee (Elsevier, 2022)
The challenge of premature non-communicable diseases (NCDs) deaths in developing countries has been attributed to late diagnosis due to limited access to preventive and primary care. Foremost in addressing this challenge is the need to develop healthcare models with low costs but guaranteeing access of healthcare. Such a need is pressing, as the invisible epidemic of NCDs continues to present a growing burden in developing countries. Point of care testing (POCT) has been identified as a powerful emerging healthcare approach which has the potential to improve healthcare access. The potential of increased NCD risk among university students calls for targeted interventions within universities. This commentary discusses the possibility of addressing the burden of NCDs by promoting the use of POCT in universities.